Do firms publish? A multi-sectoral analysis - Roberto Camerani; Daniele Rotolo; Nicola Grassano (European Commission, Joint Research Centre (JRC), 2018)
We examine corporate publishing - i.e. firms' involvement in the production of scientific publications - with two research questions. First, why do firms publish? Through systematic literature review, we propose a framework of five incentives for firms to publish: (i) accessing external knowledge and resources; (ii) attracting and retaining researchers; (iii) signalling and reputation building; (iv) supporting IP strategies; and (v) supporting commercialization strategies. Second, how does firms' engagement in publishing differ across sectors? Variation in corporate publishing has not yet been comprehensively characterized in the literature. We present an empirical analysis of the publication activity of a global sample of 2,500 firms (and the 570,000 directly owned subsidiaries of these firms) operating in 20 industrial sectors. We find that corporate publishing is widespread, though considerable heterogeneity exists within and between sectors. Most firms (84%) in our sample contributed to at least one publication from 2011 to 2015. The number of firms' publications grew over the observation period (2.3% on a yearly basis), though not as fast as the global science output in general. Firms' publications are often co-authored with researchers at academic institutions (58%) and are cited more than expected (about 12% of firms' articles are within the top 10% most cited articles). We conclude by proposing a taxonomy of sectors based on their R&D investment intensity and publication activity.
Keywords: 330; corporate publishing; incentives to publish; firm researchers; knowledge disclosure; defensive publishing; scientific publications; taxonomy